Espaces de l’insécurité : réalités territoriales et réponses locales à la délinquance - Igor Lefèvre (EchoGéo)
Based on several studies and research activities conducted by the Centre for Studies and Research on Police( CERP) from the University of Toulouse 1 Capitole, about several areas of Midi-Pyrénées, this paper seeks to present in which forms, crime and insecurity are formalized in living areas now impacted by the strong growth of the Toulouse metropolitan area. It thus questioned the relevance of the résidentialist paradigm (that is to say, the assumption of a crime would depend in form and intensity of urban, sociological , economic and demographic patterns and trends) and its impact on work organization and missions of law enforcement forces, but also all the local actors involved in security policy and crime prevention. At the level of Midi-Pyrénées, this contribution will give synthetically to know which transformations frameworks and patterns of public policies could emerge in the decade 2000-2010, in different situations, but all with a common element: the need to respond to situations perceived by local actors as risky or dangerous for the safety of citizens.